Aggregation activity of lactic acid bacteria (LAB) isolated from malaysian fermented foods - Siti Nasiroh, Ismail; Nina Suhaity, Azmi; Makky, Essam A. (Universiti Kebangsaan Malaysia, 2018)
One of important probiotic properties of Lactic Acid Bacteria (LAB) is the ability to adhere on intestinal epithelial cells. It is shown as aggregation activity of LAB. However, the probiotic properties of LAB naturally occurring in Malaysian fermented foods still remains unexplored. The aims of this study were to investigate the aggregation activity of isolated LAB from Pekasam (fermented fish), jeruk maman (fermented vegetable), tapai (fermented glutinuous rice) and tempoyak (fermented durian). Twenty isolates were identified their colony morphology, physiological and biochemical test to confirm their genus. All isolates were matched with characteristics of LAB by showing a negative catalase test, gram positive and rod shaped bacteria. They were mesophilic bacteria and survived at 1.5, 2.5, 5, 7.5 and 10 % of salt concentration. Aggregation activity of isolates was determined. Aggregation activity was increased when the incubation time increased. All isolated LAB showed best potential as probiotic. It was concluded that the results obtained from this study could contribute to the potential use of isolated LAB as a probiotic in the food and pharmaceutical industries.